P21 maintains senescent cell viability under persistent DNA damage response by restraining JNK and caspase signaling. (12th June 2017) - Yosef, Reut; Pilpel, Noam; Papismadov, Nurit; Gal, Hilah; Ovadya, Yossi; Vadai, Ezra; Miller, Stav; Porat, Ziv; Ben‐Dor, Shifra; Krizhanovsky, Valery
Abstract: Cellular senescence is a permanent state of cell cycle arrest that protects the organism from tumorigenesis and regulates tissue integrity upon damage and during tissue remodeling. However, accumulation of senescent cells in tissues during aging contributes to age‐related pathologies. A deeper understanding of the mechanisms regulating the viability of senescent cells is therefore required. Here, we show that the CDK inhibitor p21 (CDKN1A) maintains the viability of DNA damage‐induced senescent cells. Upon p21 knockdown, senescent cells acquired multiple DNA lesions that activated ataxia telangiectasia mutated (ATM) and nuclear factor (NF)‐κB kinase, leading to decreased cell survival. NF‐κB activation induced TNF‐α secretion and JNK activation to mediate death of senescent cells in a caspase‐ and JNK‐dependent manner. Notably, p21 knockout in mice eliminated liver senescent stellate cells and alleviated liver fibrosis and collagen production. These findings define a novel pathway that regulates senescent cell viability and fibrosis. Synopsis: Deletion of CDK inhibitor p21 (CDKN1A) in DNA damage‐induced senescent cells results in resumption of DNA synthesis, increased DNA damage response (DDR) and cell death, alleviating liver fibrosis in vivo . p21 maintains the viability of DNA damage‐induced senescent (DIS) cells. p21 silencing in DIS cells enhances DNA damage response via resumption of DNA synthesis. Activation of ATM induces NF‐κB/TNF‐α signalling to activate JNK kinase. Combined JNK and caspase‐3 signalling instructs DIS cell apoptosis. p21 knockout diminishes senescent cells in the fibrotic liver in vivo, reducing collagen production and fibrosis. Abstract : Deletion of p21 in senescent cells leads to increased DNA damage response and NF‐κB/JNK/caspase‐mediated cell death in vitro as well as alleviated liver fibrosis in vivo .